Keanekargaman Artropoda Tanaman Padi (Oryza sativa L.) Sistem Organik dan Konvensional di Trawas, Mojokerto, Jawa Timur: Diversity of Arthropods in Rice Plants (Oryza sativa L.) Organic and Conventional Systems in Trawas, Mojokerto, East Java - Ardiansyah, Yoyong; Widayati, Wilujeng; Windriyanti, Wiwin (Agrocentrum, 2024)
Rice is one of the various types of food plants that are predominantly cultivated as a staple food for the Indonesian people. The importance of rice plants in cultivation cannot be underestimated, considering that more than half of Indonesia's population depends on this plant as a staple food. The problem is, each rice cultivation activity is closely related to the role of arthropods, both positive and negative roles. This study was conducted in conventional and organic rice fields in Brenjonk village with an altitude of 800 meters above sea level with an area of ​​600m² slowly. The research method applied during the study was the survey method or exploration method through plant selection with purposive sampling. Research parameters were obtained through direct observation of arthropods, pitfall traps, yellow sticky traps, sweep nets, and light traps. Insect identification was carried out using literature studies with naturalist applications and insect introduction books. The results of the observations showed that arthropods were found to act as pests, predators, parasitoids, pollinators and decomposers with a diversity index (H') of insects on land A (conventional) of 0.332 and land B (organic) of 0.358, the category is classified as low diversity.